The Effect of Corporate Image and Career Development on Employee Performance with Work Commitment as A Moderating Variable at PT Rifan Financindo Berjangka Medan - Harianja , Rotua Margaretta; Siahaan, Elisabeth; Ginting, Paham (Journal of Business Management, 2025)
The development of the increasingly complex investment business requires companies to have quality human resources with a good corporate image in the eyes of the public and employees to support employee performance with career development that becomes an internal supporting factor for employees to achieve their targets. The work commitment of each employee is very much considered in order to achieve each company's goals. This research is motivated by fluctuations in employee performance which are influenced by public perception of the company's image and the lack of optimal career development in the work environment. The research method used is a quantitative approach with moderated regression analysis. Data was collected through the distribution of questionnaires to employees at PT Rifan Financindo Berjangka Medan. This study used all employees of PT Rifan as a research population with a sample of 105 people with a data collection technique using a likert scale questionnaire. The results showed that company image and career development had a positive and significant effect on employee performance, while work commitment did not play a significant role as a moderation variable even though it had a direct influence on performance. These findings confirm the importance of strengthening the company's image and sustainable career development programs as key factors in improving employee performance.